Learning organization practices and their relationship with organizational performance moderated by background variables in Yemeni Telecommunication Organizations / Ghamdan Yahya Abdullah Al-Odhari - Abdullah Al-Odhari, Ghamdan Yahya (Institute of Graduate Studies, UiTM, 2013)
This study aims to explore learning organization practices and their relationship with organizational performance in Yemeni Telecommunication Organizations (YTOs). A survey approach using a version of Arabic translated Dimensions of the Learning Organization Questionnaire (DLOQ) developed by Watkins and Marsick (1993) that implies seven characteristics to the development of a learning organization, namely, continuous learning, inquiry and dialogue, teamwork, embedded systems, empowerment, systems connections, and provision of leadership are used. Five communication organizations were participated in this study (3 local: Public Yemeni Telecommunication, TeleYemen, and Yemen Mobile; and 2 Foreign: SabaFon and MTN). A total of 577 questionnaires were distributed, to employees at both senior and middle levels, and 447 questionnaires were returned with a response rate of 77.5%. Results of the study revealed that the practices of the seven dimensions showed low especially empowerment, while the highest dimension was continuous learning. Correlation analysis showed that all of the correlation coefficients were significant at the .01 level, and with an overall medium positive relationship with financial performance while large with knowledge performance…